Phenolic compounds with antioxidant capacity of the native Andean potato (Solanum tuberosum L.) Huagalina variety in La Libertad - Peru (Scientia Agropecuaria, 2016)
Potato is grown and consumed throughout the world for their particular calorific nutritional value and vitamin C, but it also contains phytochemicals (secondary metabolites) that have been studied and found to have positive effects in preventing degenerative diseases in human health, such as hypertensive activity, and also atherosclerosis, type 2 diabetes, liver fibrosis, Alzheimer's disease, macular degeneration and cancer. We aimed to identify and quantify phenolic compounds in potatoes grown on El Zuro (EZ) and Huayatan Alto (HA) in Santiago de Chuco, La Libertad, Peru. The field trials were carried out in EZ (altitude 3750 m.a.s.l.) and HA (altitude 3150 m.a.s.l.) employing organic and inorganic fertilization respectively. Extraction from the peel and flesh was obtained separately, with the following solution: 50% methanol, 50% deionized water and 0.5% acetic acid. The sample was injected into the system UPLC - MS / MS, using ESI ionization (Electrospray Ionization) and fifteen external reference standards. Thirteen metabolites were detected in the flesh and potato peel. The highest content of secondary metabolites (mg/100 g DW) were: Chlorogenic acid (476.82 ± 63.58), neochlorogenic acid (87.90 ± 19.42) caffeic acid (77.53 ± 14.49) and vanillin (11.52 ± 1.38). The PCA (Principal Components Analysis) scores show that the highest concentration of metabolites was found in the peel of both cultivars. We concluded that the native potato Huagalina contains the genes expressed in different biosynthetic pathways of the metabolites found in this study.
Keywords: native potato; phytochemicals; cancer; diabetes; chlorogenic acid